Research on Contamination of Foods with Mercury Mining: A Ten-Year (2011-2020) Bibliometric Analysis. Issue 1 (November 2021) - Zuas, O; Elishian, C; Darmayanti, N T E; Budiman, H; Yaumidin, U K
Abstract: The first study on bibliometric network analysis of research on contamination of foods with mercury (Hg) mining is presented. The Hg mining has been reported as the primary source of toxic Hg contamination of foods. The living population's exposure to Hg is highly associated with the consumption of Hg-contaminated foods and water. This study aims to explore the global scientific literature to gain insight into how the scientific literature addresses contamination of foods with Hg mining using bibliometric network analysis. The study was conducted on 319 documents from publications indexed in the Scopus database from 2011 to 2020. We collected reviewed documents using various techniques to analyze this issue, including general statistics, bibliometrics, and analytics. According to analysis results, several significant findings were found as follows. The co-authorship network demonstrates the relationship among authors and countries regarding contamination of foods with Hg mining. Co-authorship authors and country analysis indicate that "Chinese authors" and "the Chinese Academic of Sciences" are the first among the most influential authors and institution, respectively. Moreover, from systematic visualization of co-occurrence keywords and clustering analyses, six major clusters were reviewed and have been identified as potential opportunities for future research.